Varieties of insecurity and rebel-civilian ties across time: Evidence from post-war Zimbabwe - Shelley Liu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Literature on rebel governance has examined various ways in which rebels engage with civilians, build informal governing institutions, and exert social control during civil war. When rebels win, how does rebel governance affect post-war politics? This paper explores how varieties of insecurity that the victor faces after war-external threat, internal challengers, or electoral politics-explain the role of rebel-civilian ties in helping the new ruling party to successfully consolidate power. I examine forty years of rebel government rule in Zimbabwe, where the Zimbabwe African National Union-Patriot Front (ZANU-PF) faced different threats at different points in time from its wartime rivals, ex-combatants, and opposition parties. ZANU-PF's strategies to eliminate these threats illustrate how rebel governance and rebel-civilian ties affect post-war politics differently based on ruling party constraints.
Keywords: 330; rebel victory; rebel governance; conflict legacies; rebel-to-party transition; Zimbabwe; process tracing